Active infection with Helicobacter pylori in healthy couples. - Brenner, H. (Cambridge University Press, 1999)
The mode of spread of Helicobacter pylori infection is subject to ongoing debate. Recent studies among patients with gastrointestinal disorders suggest a potential role of conjugal transmission. In this study, the clustering of H. pylori infection was assessed among 110 employees of a health insurance company and their partners. Active infection with H. pylori was measured by the 13C-urea breath test. Information on potential confounders was collected by a standardized questionnaire. Overall, 16 employees (14.5%) and 24 partners (21.8%) were infected. While only 7% (6/86) of employees with an uninfected partner were infected, this applied to 42% (10/24) of employees with an infected partner. A very strong relation between partners' infection status persisted after control for age and other potential confounders (adjusted odds ratio, 7.0; 95% confidence interval, 1.8-26.7). Furthermore, the risk of infection increased with the number of years lived with an infected partner. These results support the hypothesis of a major role of spouse-to-spouse transmission of H. pylori infection.